2008
DOI: 10.1128/jvi.02579-07
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Transmitted Drug Resistance among Subjects with Primary Human Immunodeficiency Virus Infection

Abstract: Following interruption of antiretroviral therapy among individuals with acquired drug resistance, preexisting drug-sensitive virus emerges relatively rapidly. In contrast, wild-type virus is not archived in individuals infected with drug-resistant human immunodeficiency virus (HIV) and thus cannot emerge rapidly in the absence of selective drug pressure. Fourteen recently HIV-infected patients with transmitted drug-resistant virus were followed for a median of 2.1 years after the estimated date of infection (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
180
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 198 publications
(199 citation statements)
references
References 48 publications
16
180
3
Order By: Relevance
“…Six hundred four blood samples were collected longitudinally from 108 recently HIV-infected participants from the San Diego Primary Infection Resource Consortium [18] between October 1996 and October 2012. All participants were CMV and EBV seropositive.…”
Section: Participants Samples and Clinical Laboratory Testsmentioning
confidence: 99%
“…Six hundred four blood samples were collected longitudinally from 108 recently HIV-infected participants from the San Diego Primary Infection Resource Consortium [18] between October 1996 and October 2012. All participants were CMV and EBV seropositive.…”
Section: Participants Samples and Clinical Laboratory Testsmentioning
confidence: 99%
“…Hence, first-line NNRTIs available in Lebanon will fail at controlling HIV-1 infection among these participants. M46I, known as a stable mutation hampering PI-based antiretroviral regimens [41], was not detected in any of our study participants; moreover, L90M, a frequently reported mutation, was detected in one patient. Our results indicate that the use of recommended treatment regimen will fail at controlling HIV-1 among the study participants as indicated by the type of detected HIVDR mutations.…”
Section: Discussionmentioning
confidence: 94%
“…TDR mutations may have been underestimated as low prevalence mutations are not detected by most standard sequencing techniques unless the mutation is present in >10-30% of the population (Bellecave et al, 2013;Johnson et al, 2008). In some cases, the wild-type virus may become the dominant virus and certain TDR mutations may not be detected in the absence of selective drug pressure, though this may occur only after several years (Gandhi et al, 2003;Little et al, 2008;Yerly et al, 2008). It is possible the TDR rate in Washington, D.C. may be higher than the observed rate of 17%.…”
Section: Discussionmentioning
confidence: 99%